A new thelastomatid of the genus Blatticola Schwenk, 1926 (Nematoda, Thelastomatidae) a parasite of cricket (Orthoptera, Gryllidae) from Argentina - Camino, Nora Beatriz (2009)
Blatticola biannulata n. sp. (Oxyurida, Thelastomatidae) a parasite of the cricket Anurogryllus muticus (De Geer)(Orthoptera, Gryllidae) from Argentina, is described and illustrated. This is the second species of the genusBlatticola found parasitizing cricket. Females of this new species is characterized by the cuticle that is annulatedfrom the anterior end up to the middle of the body, the mouth opening being subtriangular in shape surroundedby 8 cephalic papillae, the short stoma with two semicircles sclerotised and the telostoma with onemovable tooth, small pore shaped amphids, an oesophagus divided into three parts, anterior cylindrical corpus,isthmus distinct, and basal bulb valvated, the nerve ring situated arounded the isthmus, the intestine broadestanteriorly, eggs oval, smooth shell, in apical view show a triangular section, with three wings, the dorsal oneand two lateroventrals, males with one pair of preanal, and two pairs of postanal papillae, and the tail appendageshort, conical and pointed, the female has in the top an structure of anchorage, like structure of grasp.